Three-dimensional measurement of the depth of invasion in oral squamous cell carcinoma samples using Lugol's iodine-enhanced micro-computed tomography: an original study - Jiaxin Yu; Zhouyu Gu; Lichan Wang; Qian Zhang; Yumei Pu; Qingang Hu; Chengwan Xia; Yuxin Wang (Journal of Applied Oral Science)
Abstract Objectives: Depth of invasion (DOI) in oral squamous cell carcinoma (OSCC) guides treatment and prognosis but lacks three-dimensional (3D) insight. Thus, this study aimed to investigate the feasibility and accuracy of Lugol's iodine-enhanced micro-computed tomography (CT) for the 3D measurement of DOI in OSCC samples. Methodology: In total, 50 in vitro OSCC samples from Nanjing Stomatological Hospital (July 2022 to January 2024) were subjected to micro-CT imaging with a slice thickness of 50 μm following 3% Lugol iodine staining for 12 h, followed by pathological examination and staining. The panoramic diagnostic scanner digitally measured pathological DOI. The micro-CT DOI was measured by evaluating the voxel value of the boundary of the tumor lesion and comparing it with the pathological examination results. Experienced physicians analyzed both measurements, and statistical analyses were performed to determine their correlation. Results: Lugol iodine-enhanced micro-CT imaging distinguishes various tissue structures, such as tumor tissue, epithelial tissue, muscle tissue, blood vessel structure, and other major tissue structures in 3D space. This imaging technique found and localized micro-tumor lesions (1.82×1.5×1 mm3) when in conjunction with pathological sections. Statistical analysis indicated a strong correlation between pathological DOI and micro-CT DOI (P<.001; r=0.986). During DOI measurement, Lugol iodine-enhanced micro-CT imaging effectively compensated for the loss of 3D space information in the pathological measurements, improving the accuracy of the DOI measurement. Conclusions: Lugol iodine-enhanced micro-CT improves OSCC DOI 3D measurements, enhances pathological staging accuracy, and aids treatment decisions and prognosis.